Spectrum of mutations in aspartylglucosaminuria. - Ikonen, E (1991)
Aspartylglucosaminuria (AGU) is an inherited lysosomal storage disorder caused by the deficiency of aspartylglucosaminidase. We have earlier reported a single missense mutation (Cys163----Ser) to be responsible for 98% of the AGU alleles in the isolated Finnish population, which contains about 90% of the reported AGU patients. Here we describe the spectrum of 10 AGU mutations found in unrelated patients of non-Finnish origin. Since 11 out of 12 AGU patients were homozygotes, consanguinity has to be a common denominator in most AGU families. The mutations were distributed over the entire coding region of the aspartylglucosaminidase cDNA, except in the carboxyl-terminal 17-kDa subunit in which they were clustered within a 46-amino acid region. Based on the character of the mutations, most of them are prone to affect the folding and stability and not to directly affect the active site of the aspartylglucosaminidase enzyme.